2008
DOI: 10.1007/s10482-008-9289-0
|View full text |Cite
|
Sign up to set email alerts
|

Lead(II) resistance in Cupriavidus metallidurans CH34: interplay between plasmid and chromosomally-located functions

Abstract: Proteome and transcriptome analysis, combined with mutagenesis, were used to better understand the response of Cupriavidus metallidurans CH34 against lead(II). Structural Pb(II)-resistance genes of the pMOL30-encoded pbrUTRABCD operon formed the major line of defense against Pb(II). However, several general stress response mechanisms under the control of alternative sigma factors such as sigma24/rpoK, sigma32/rpoH and sigma28/fliA were also induced. In addition, the expression of the pbrR(2) cadA pbrC(2) opero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
66
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 29 publications
0
66
0
Order By: Relevance
“…S1 in the supplemental material). The three P IB2 -type ATPases (TC 3.A.3) ZntA, CadA, and PbrA remove Zn 2ϩ , Cd 2ϩ , and Pb 2ϩ , respectively, from the cytoplasm (4,7,24,49,51,56 , respectively, from the cytoplasm to the periplasm to feed additional substrate cations into the RND-driven efflux systems (2,3,51). Up to four P IB1 -type ATPases, two RNDdriven efflux systems, and a variety of other proteins maintain copper homeostasis (31) and may also be involved in silver and gold transformation (22,47).…”
Section: Discussionmentioning
confidence: 99%
“…S1 in the supplemental material). The three P IB2 -type ATPases (TC 3.A.3) ZntA, CadA, and PbrA remove Zn 2ϩ , Cd 2ϩ , and Pb 2ϩ , respectively, from the cytoplasm (4,7,24,49,51,56 , respectively, from the cytoplasm to the periplasm to feed additional substrate cations into the RND-driven efflux systems (2,3,51). Up to four P IB1 -type ATPases, two RNDdriven efflux systems, and a variety of other proteins maintain copper homeostasis (31) and may also be involved in silver and gold transformation (22,47).…”
Section: Discussionmentioning
confidence: 99%
“…Its genome, made out of two chromosomes and two megaplasmids, was sequenced and thoroughly analyzed (Janssen et al 2010). While the study of metal resistance determinants in CH34 initially focused on the bacterium's two megaplasmids pMOL28 and pMOL30, the importance of chromosomal genes was acknowledged in later studies (Legatzki et al 2003;Grosse et al 2004;Munkelt et al 2004;Nies et al 2006;Taghavi et al 2008). It is noteworthy that many heavy metal resistance determinants are linked to genomic islands and transposons present on the bacterium's four replicons (Monchy et al 2007;Mergeay et al 2009;).…”
Section: Introductionmentioning
confidence: 99%
“…We also found that there was only slight Pb(II)-inducible expression from PpbrA in AE104, which lacks both pMOL28 and pMOL30. This suggests that there may be a very low level of cross-regulation of pMOL30 PpbrA by PbrR 2 (R_met2302) and/or PbrR 3 (R_met3456) [(previously known as PbrR691 and PbrR710, respectively (Taghavi et al 2009)], but sequential deletion of PbrR family regulators in CH34 would be required to determine unambiguously which promoters previously identified as being targets for PbrR regulators are activated by them. Levels of Pb(II) required for induction of PpbrA are Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There is a precedent for this model with MerD competing for PmerT with MerR (reviewed in Hobman et al 2005). Regulatory cross-talk between different metal-sensing regulators and promoters in C. metallidurans is one explanation of recent transcriptomic data that showed expression of diverse metal ion resistance genes in response to single metal ions, but RNA polymerase r 24 , r 28 and r 32 sigma factors are also postulated as being responsible for this effect (Monchy et al 2007;Taghavi et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation